The Influence Of CAR, BOPO, NIM, FDR And DPK On The Profitability Of Commercial Banking Listed On The Indonesian Stock Exchange (BEI) - Tiara Sanika Putri; Yudi Partama Putra; Hesti Setiorini (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2024)
This research aims to determine the factors that influence the profitability of general banking listed on the Indonesia Stock Exchange (BEI). Capital Adequacy Ratio , Operating Costs Operating Income, Net Interest Margin , Financing to Deposit Ratio , and Third Party Funds as independent variables while profitability as the dependent variable is measured using the ROA measurement indicator. The population in this research are general banking companies registered on the IDX for the 2015-2021 period and the samples used in this research were taken using a purposive sampling method , namely a sampling technique that takes into account certain criteria data that are adapted to the research objectives. The samples in this research are financial reports and annual reports of banking companies starting from 2015-2021 consisting of 33 companies that meet the criteria, and based on the research year period there are 23 1 samples. Methods of data collection using documentation. Data analysis used is descriptive statistical test and hypothesis testing using panel data regression. The results of this study indicate that partially the Capital Adequacy Ratio , Net Interest Margin , Financing to Deposit Ratio , and Third Party Funds do not have a significant effect on profitability as measured by ROA, while Operational Costs and Operational Income have an effect on profitability as measured by ROA, and simultaneously CAR , BOPO, NIM, FDR and DP K have a joint effect on profitability.